The phase transitions behavior and defect structure evolution in magnesium hydride/single-walled carbon nanotubes composite at hydrogen sorption-desorption processes; Journal of Alloys and Compounds; Vol. 953 - Kudiyarov V. N. Victor Nikolaevich; Elman R. R. Roman Romanovich; Kurdyumov N. Nikita; Laptev R. S. Roman Sergeevich (2023, 2023)
Title screen